Signs of the times - Shroyer, Edgar H. (Gallaudet University Press, 2011)
"The bestselling American Sign Language textbook Signs of the Times has been completely revised and updated. The new, second edition is an excellent beginner's American Sign Language textbook designed for use in the classroom or at home. Organized into 44 lessons, it presents more than 1,300 signs representing 3,500 English glosses. Each lesson contains clear illustrations of all signs, English equivalent words and synonyms, sample sentences to define vocabulary context, and practice sentences to display and reinforce ASL usage. Signs of the Times is a complete text that includes new class activities for teachers, plus new student activities that can be done in class, as homework, or as quizzes. The new edition features the Contextual Sign/Word Appendix, which displays groups of sentences using the same English word to show different meanings along with the corresponding ASL signs. It also provides an expanded index, vocabulary lists, and a reading reference list. The new edition offers facts on ASL grammar and Deaf culture and includes mind ticklers that enliven the lessons with hints, tips, and mnemonic devices."--Publisher's website.